(untitled) (Third Sector Social Economic Review, 2017)
Another issue as important as payment of the tax obligations for the taxpayers is fulfillment of the set of formal duties. According to Tax Procedure Law formal duties are clearly defined but in practice it is observed that in some cases aforementioned responsibilities cannot be fulfilled completely time to time. In this study, it is aimed to lead cooperatives, unions of breeders that are qualified as cooperatives and unions of agricultural producers that are qualified as associations to fulfill their taxational duties completely and to inform them about the possible sanctions which can be confronted in case of not fulfilling those duties as specified.